Quantitative Proteomic Profiling of Marine Diatom Skeletonema dohrnii in Response to Temperature and Silicate Induced Environmental Stress - Thangaraj, Satheeswaran; Palanisamy, Satheesh Kumar; Zhang, Guicheng; Sun, Jun (Frontiers in Microbiology, 2021)
Global warming is expected to reduce the nutrient concentration in the upper ocean and affect the physiology of marine diatoms, but the underlying molecular mechanisms controlling these physiological changes are currently unknown. To understand these mechanisms, here we investigated iTRAQ based proteomic profiling of diatom Skeletonema dohrnii in a multifactorial experimental with a combining change of temperature and silicate concentrations. In total, 3369 differently abundant proteins were detected in four different environmental conditions, and the function of all proteins was identified using Gene Ontology and KEGG pathway analysis. For discriminating the proteome variation among samples, multivariate statistical analysis (PCA, PLS-DA) was performed by comparing the protein ratio differences. Further, performing pathway analysis on diatom proteomes, we here demonstrated downregulation of photosynthesis, carbon metabolism and ribosome biogenesis in the cellular process that leads to decrease the oxidoreductase activity and affects the cell cycle of diatom. Using PLS-DA VIP score plot analysis, we identified fifteen protein biomarkers for discriminating studied samples. Of these, five proteins or gene (rbcL, PRK, atpB, DNA-binding and signal-transduction) identified as key biomarkers, induced by temperature and silicate stress in diatom metabolism. Our results show that proteomic finger-printing of S. dohrnii with different environmental conditions adds biological information that strengthens marine phytoplankton proteome analysis.